An ion-in-conjugation polymer enables the detection of NO2 with parts-per-trillion sensitivity and ultrahigh selectivity. Issue 3 (18th December 2019) - Yu, Chuang; Lin, Hong-Zhen; Zhou, Jin; Cheng, Xue-Feng; He, Jing-Hui; Li, Hua; Xu, Qing-Feng; Li, Na-Jun; Chen, Dong-Yun; Lu, Jian-Mei
Abstract : The detection of nitric dioxide (NO2 ) at the parts-per-trillion (ppt) level is critical for both environmental monitoring and human health. Abstract : The detection of nitric dioxide (NO2 ) at the parts-per-trillion (ppt) level is critical for both environmental monitoring and human health. However, none of the chemiresistors reported to date can detect NO2 at the parts-per-trillion (ppt) level due to the low sensitivity of the sensory materials. In this work, an ion-in-conjugation polymer para -polyphenylsquaraine ( p -PPS) was designed and fabricated into an NO2 chemiresistor. The sensor had the highest sensitivity of 1450 ppm −1 (at 100 ppb) and the lowest detection limit of 40 ppt among all reported chemiresistors. In addition, p -PPS showed ultrahigh selectivity, where other interfering gases had less than 1/1887th of the signal of NO2 under the same concentration (10 ppm). Calculations, in situ infrared spectroscopy and sum frequency generation spectroscopy (SFG) revealed that the ion-in-conjugation-inspired H-bonding between p -PPS and NO2 led to such high sensitivity. Our results highlight the potential of the concept of ion-in-conjugation in the design of highly sensitive gas sensory materials.